Expediting Manufacturing Launch Using Integrated Data With AI/ML Analytic Solutions - Helen Haiying Yu; Scott Martin; Laurenz van der Meer; Edward Yang; Sherry Lee; Wanting Xiong; Vaishnavi Reddipalli; Richard Burch; Tomonori Honda; Jeffrey David (IEEE Journal of the Electron Devices Society, 2025)
Manufacturing yield, test time and quality are important metrics in new product introduction (NPI) to manufacturing safe launch. A powerful yield management system is crucial to achieve the goal metrics. In this paper, recommended yield management system selection criteria, data integration and machine learning (ML) methodologies along with innovative ways of using the selected yield management system to benefit safe manufacturing launch efficiency are introduced. Three examples of using a cloud yield tool including ML capabilities to expedite yield learning, test time reduction (TTR) and quality enhancement are presented.